(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Dr. Deepak Shrivastava, Professor and Principal, IMI Pharmaceutical Studies, Indore, Madhya Pradesh, India Abstract Treatment algorithms for cardiovascular disorders rely on evidence-based, stepwise clinical pathways. The management of hypertension begins with accurate diagnosis and ASCVD risk stratification, followed by foundational lifestyle modifications. Pharmacological therapy is then initiated, guided by blood pressure targets and compelling indications, often requiring stepwise addition of first-line agents like diuretics, CCBs, or RAS-blockers. Coronary artery disease management is bifurcated: stable ischemic heart disease is managed with guideline-directed medical therapy (GDMT) for event prevention and symptom control, whereas acute coronary syndromes (ACS) demand time-sensitive reperfusion for STEMI or risk-based invasive strategies for NSTEMI. Heart failure algorithms are stratified by ejection fraction. HFrEF management is built on four concurrent pillar therapies—ARNI/ACEi/ARB, beta-blockers, MRAs, and SGLT2 inhibitors. HFpEF management centers on SGLT2 inhibitors and rigorous comorbidity control. The approach to atrial fibrillation rests on three pillars: anticoagulation based on stroke risk, rate control, and rhythm control strategies. Algorithms for ventricular arrhythmias are dictated by hemodynamic stability, prioritizing defibrillation for unstable patients and ICDs for long-term prevention. Valvular heart disease interventions, whether surgical or transcatheter, are primarily triggered by the onset of symptoms or objective evidence of ventricular dysfunction.. Keywords: Cardiovascular Algorithms, Guideline-Directed Medical Therapy (GDMT), Hypertension, Acute Coronary Syndrome, Heart Failure VIEW PDF